Hydrological variations associated with geomorphological changes in a sand-dune barrier of the Partido de la Costa, province of Buenos Aires - Carretero, Silvina Claudia (2017)
Fil: Carretero, Silvina Claudia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Cátedra de Hidrología General; Argentina